Editorial - Kouis, Dimitris (Journal of Integrated Information Management, 2024)
The first paper explores the goal and potential of integrating machine learning technologies into archives and records management practices. Placing the subject classification of records at the center of the discussion, this paper presents a research hypothesis. It highlights the necessity of deepening the standardisation of government actions record management processes. Thus, readers have a deeper understanding of the transformative role that machine learning technologies can play in archives and records management, future practices and decision-making in the field. The second paper studies the effect of photos on cultural technologies. Researchers used ancient museum objects with contemporary photos, showing people performing similar activities in antiquity and today. Qualitative data from interviews were collected and when they saw the images of ancient objects and contemporary photos. Photos can function as interpretation aids and also allow participants to make multiple connections between past and present, across societies and cultures, between current and prior knowledge, and permit connections to personal experience, leading to the conclusion that critical constructivist approaches take place when people are presented with the two images and meaning-making processes. The last paper presents the adaptation of VIVO by the University of West Attica. Researchers have merged the existing systems and harvested research-related information from different sources on the web to create an ontology-based system for documenting the undertaken research within an institution. This solution offers the possibility for the personalisation of the ontology, thus making it possible to customise the repository to fit an ed significant components for the University, as well as the information visualisation.